Answer:
3 sips = 1 gulp
Explanation:
We will solve this problem using the given simultaneous equations. We will use either substitution or elimination. For this problem, we will use elimination.
Let s = No. of sips
Let g = No. of gulps
5s + 4g = 1 -> (1)
13s + 7g = 2 -> (2)
We will multiply the first equation by 7 and multiply the second equation by 4 so that both equations have '28g'.
5s + 4g = 1 -> (1) × 7
13s + 7g = 2 -> (2) × 4
------------------------------
35s + 28g = 7
52s + 28g = 8
We will subtract the second equation from the first equation.
- 17s = - 1
s = - 1 / - 17
s = 1 / 17
We will substitute the obtained value for 's' into the first equation to solve for 'g'.
5 ( 1 / 17 ) + 4g = 1 -> (1)
5 / 17 + 4g = 1
4g = 1 - 5 / 17
g = ( 12 / 17 ) / 4
g = 3 / 17
Therefore, as 3 / 17 ÷ 1 / 17 = 3:
3 sips = 1 gulp